The Relationship Between Knowledge And Nutritional Status With The Incidence Of Edema During Pregnancy - Hasritawati, Hasritawati; Madeni, Barirah (JKM (Jurnal Kebidanan Malahayati), 2024)
Latar Belakang: Gizi ibu hamil perlu mendapat perhatian karena sangat berpengaruh pada perkembangan janin yang dikandungnya. Pada masa kehamilan gizi ibu hamil harus memenuhi kebutuhan gizi untuk dirinya dan untuk pertumbuhan serta perkembangan janin karena gizi janin tergantung pada gizi ibu, sehingga kebutuhan gizi ibu juga harus tetap terpenuhi.Tujuan: Mengetahui ada hubungan pengetahuan dan status gizi dengan kejadian kek pada masa kehamilan di Puskesmas Bebesan.Metode:  Penelitian  dilakukan  penelitian deskritif analitik dengan pendekatan cross sectional.Populasi pada penelitian ini adalah seluruh ibu hamil di Puskesmas Bebesan. Sampel penelitian melibatkan 30 ibu hamil di Puskesmas Bebesan dan eseha sampling accidental sampling. Analisis data pada penelitian ini menggunakan analisis univariat dan bivariat yang menggunakan software SPSS untuk melakukan uji chi square.Hasil: Hasil analisis statistik didapatkan ada hubungan pengetahuan dan status gizi  dengan kejadian kek pada masa kehamilan di Puskesmas Bebesan dengan nilai p = 0,00 < α = 0,05.Kesimpulan: Terdapat hubungan antara positif antara pengetahuan dan status gizi dengan kejadian kek pada masa kehamilan di Puskesmas Bebesan.Saran: Agar tenaga kesehatan memberikan edukasi sehingga meningkatkan pengetahuan ibu hamil dan memperhatikan status gizi ibu hamil. Kata Kunci : Pengetahuan, Status Gizi, Ibu Hamil, Kekurangan Energi Kronis ABSTRACT Background: The nutrition of pregnant women needs attention as it significantly affects the development of the fetus they are carrying. During pregnancy, the nutrition of pregnant women must meet the nutritional needs for themselves and for the growth and development of the fetus because the fetus's nutrition depends on the mother's nutrition, so the mother's nutritional needs must also be met.Purpose:  To determine the relationship between knowledge and nutritional status with the incidence of chronic energy deficiency during pregnancy at Bebesan Health Center.Methods:  The research was conducted using descriptive analytic research with a cross-sectional approach. The population in this study was all pregnant women at Bebesan Health Center. The research sample involved 30 pregnant women at Bebesan Health Center using accidental sampling technique. Data analysis in this study used univariate and bivariate analysis using SPSS software to conduct chi-square tests.Results: The results of the statistical analysis showed a relationship between knowledge and nutritional with the incidence of chronic energy deficiency during pregnancy at Bebesan Health Center with .p value status p = 0.00 < α = 0.05.Conclusion: There is a positive relationship between knowledge and nutritional status with the incidence of chronic energy deficiency during pregnancy at Bebesan Health Center.Suggestions: Health professionals should provide education to improve the knowledge of pregnant women and pay attention to the nutritional status of pregnant women. Keywords: : Knowledge, Nutritional Status, Pregnant Women, Chronic Energy Deficiency